Chemical Composition and Bioactive Compounds of Some Wild Edible Mushrooms - Melinda NAGY (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2017)
Over the last decades, the consumption of mushrooms has significantly increased due to the scientific evidence of their ability to help the organism in the combat and prevention of several diseases (Kalac, 2009). Fruiting bodies of mushrooms are consumed as a delicacy for their texture and flavour, but also for their nutritional properties that makes them even more attractable (Heleno S. 2015). In this paper data were collected from several scientific studies with the aim to characterize the chemical composition and content of bioactive compounds of various mushrooms species: Agaricus bisporus, Boletus edulis, Cantharellus cibarius, Pleurotus ostreatus, Lactarius piperatus. The chemical composition of 5 wild edible studied mushrooms, including moisture, ash, total carbohydrates, total sugars, crude fat, crude protein and energy were determined according to AOAC procedures.